Synergistic co-digestion of solid-organic-waste and municipal-sewage-sludge: 1 plus 1 equals more than 2 in terms of biogas production and solids reduction. (15th December 2015) - Aichinger, Peter; Wadhawan, Tanush; Kuprian, Martin; Higgins, Matthew; Ebner, Christian; Fimml, Christian; Murthy, Sudhir; Wett, Bernhard
Abstract: Making good use of existing water infrastructure by adding organic wastes to anaerobic digesters improves the energy balance of a wastewater treatment plant (WWTP) substantially. This paper explores co-digestion load limits targeting a good trade-off for boosting methane production, and limiting process-drawbacks on nitrogen-return loads, cake-production, solids-viscosity and polymer demand. Bio-methane potential tests using whey as a model co-substrate showed diversification and intensification of the anaerobic digestion process resulting in a synergistical enhancement in sewage sludge methanization. Full-scale case-studies demonstrate organic co-substrate addition of up to 94% of the organic sludge load resulted in tripling of the biogas production. At organic co-substrate addition of up to 25% no significant increase in cake production and only a minor increase in ammonia release of ca. 20% have been observed. Similar impacts were measured at a high-solids digester pilot with up-stream thermal hydrolyses where the organic loading rate was increased by 25% using co-substrate. Dynamic simulations were used to validate the synergistic impact of co-substrate addition on sludge methanization, and an increase in hydrolysis rate from 1.5 d −1 to 2.5 d −1 was identified for simulating measured gas production rate. This study demonstrates co-digestion for maximizing synergy as a step towards energy efficiency and ultimately towards carbon neutrality. Graphical abstract: Highlights: Full-scale case studies showing additional synergetic gas-production from co-digestion. Co-substrate VS-addition up to 25% boosts methane without additional cake production. Digester-loads up to 6.7 kg(VS)m −3  d −1 have been demonstrated. Model-based analysis indicated mechanism of synergy as increase in hydrolysis speed.